Correlation between interleukin-1β and matrix metalloproteinase-1 levels in crevicular fluid with a proposed periodontal disease index in children - Juan Manuel Guízar-Mendoza; Christian Andrea LÓpez-Ayuso; Laura Anguiano-Flores; Martha Eugenia Fajardo-Araujo; Norma Amador-Licona (Wolters Kluwer Medknow Publications, 2018)
Background: The crevicular fluid contains biomarkers that allow the identification of periodontal disease, anticipation of its risk, and prediction of its progression. Purpose: The purpose of this study is to correlate interleukin-1β (IL-1β) and matrix metalloproteinase-1 (MMP-1) levels in crevicular fluid with periodontal disease severity in schoolchildren. Methods: A cross-sectional study was conducted in 82 schoolchildren between 9 and 12 years. The biofilm percentage, attachment level, gingival recession, dental calculus, and bleeding on probing were measured in the teeth 16, 26, 36, 41, and 46. These five parameters obtained were considered to propose a disease score between 0 and 10 points. In crevicular fluid from the tooth with the highest score, IL-1β and MMP-1 levels were measured. Results: According to the proposed score, mild gingivitis was identified in 20 schoolchildren, moderate gingivitis in 30, and severe gingivitis in 32. Biofilm percentage, IL-1β, and MMP-1 levels increased as the severity of the disease increase. The mean and 95% confidence interval were 23.2 pg/μl (18.6-27.7), 37.3 pg/μl (27.8-46.9), and 44.6 pg/μl (34.4-58.8) (P = 0.01) for IL-1β and 2.69 mol/min (2.51-2.87), 4.43 mol/min (3.9-4.95), and 5.59 mol/min (4.81-6.38) (P < 0.001) for MMP-1 in each group, respectively. The proposed clinical score correlated with biofilm percentage (r = 0.63), IL-1β (r = 0.50), and MMP-1 (0.45) levels, P < 0.001 in all cases. Conclusions: The proposed clinical score for periodontal disease in children correlated with percentage of biofilm, IL-1β, and MMP-1 levels.